Influence of Lecturers Perception of Internet Service Quality in Nigeria Higher Education - Abu Ziden, Azidah; Emmanuel Ifedayo, Adu; Binti Ismail, Aziah (International Journal of Psychosocial Rehabilitation, 2020)
Internet service quality is a factor in Nigerian higher education that holds several challenges for lecturers. This study adopted and adapted a service-oriented framework to examine factors influencing lecturers perceived internet service quality (LPISQ). Hence, this research considered the influence of lecturers perceived internet service (LPIS) and lecturers expected internet service (LEIS) on lecturers’ perceived internet service quality (LPISQ). The reason being that expected service and perceived service influence perceived service quality in the service-oriented framework introduced in this study. This study involved quantitative methods, which utilized a survey approach. This study gathered one hundred and thirteen (113) questionnaire responses. This study result showed that lecturers perceived internet service (LPIS) is a significant influence on lecturers perceived internet service quality (LPISQ). However, lecturers expected internet service (LEIS) to have an insignificant influence on lecturers’ perceived internet service quality (LPISQ). This study hypothesis was tested at the .05 level of significance. Based on this study’s findings, the relevant conclusion was made.